2009
DOI: 10.1002/adsc.200800685
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Deoxygenation of 1,2‐Propanediol to Give n‐Propanol

Abstract: Deoxygenation of 1,2-propanediol (1.0 M in sulfolane) catalyzed by bis(dicarbonyl)(m-hydrido)(pentamethylcyclopentadiene)ruthenium trifluo-+ OTf À ) (0.5 mol%) at 110 8C under hydrogen (750 psi) in the presence of trifluoromethanesulfonic acid (HOTf) (60 mM) gives n-propanol as the major product, indicating high selectivity for deoxygenation of the internal hydroxy group over the terminal hydroxy group of the diol. The deoxygenation of 1,2-propanediol is strongly influenced by the concentration of acid, giving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 55 publications
2
62
0
Order By: Relevance
“…In the previous report, the conversion of 1,2-PrD to 1-PrOH can proceed by the acid-catalyzed dehydration of 1,2-PrD to propionaldehyde and the subsequent hydrogenation of propionaldehyde to 1-PrOH. [19] In the previous case, HOTf was used as an acid catalyst. The acid catalyst promoted 1,2-PrD conversion, however, it also catalyzed ether formation such as di-n-propyl ether and propylene glycol propyl ether.…”
Section: Optimization Of the Additive And Its Amountmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous report, the conversion of 1,2-PrD to 1-PrOH can proceed by the acid-catalyzed dehydration of 1,2-PrD to propionaldehyde and the subsequent hydrogenation of propionaldehyde to 1-PrOH. [19] In the previous case, HOTf was used as an acid catalyst. The acid catalyst promoted 1,2-PrD conversion, however, it also catalyzed ether formation such as di-n-propyl ether and propylene glycol propyl ether.…”
Section: Optimization Of the Additive And Its Amountmentioning
confidence: 99%
“…It should be noted that the homogeneous Ru catalyst with HOTf for the conversion of 1,2-PrD is not active for the deoxygenation of glycerol. [19] One-pot conversion of glycerol to propanols is a characteristic of the RhÀReO x /SiO 2 catalyst. Figure 8 shows X-ray diffraction (XRD) patterns of RhÀReO x / SiO 2 (Re/Rh = 0.5) and Rh/SiO 2 after the catalytic use.…”
Section: Optimization Of the Additive And Its Amountmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also reports [46][47][48][49][50][51][52] on the use of homogeneous ruthenium catalysts in combination with triflic acid (HOTf) and sulfolane as the solvent for the selective hydrodeoxygenation of a secondary alcohol in the presence of a primary alcohol. For example, Schlaf et al [51] reported the production of 1-propanol from 6 using [{Cp*Ru(CO) 2 While preparing this manuscript, Dumesic et al [44] reported hydrodeoxygenation reactions of various diols and triols using bimetallic Rh-ReO x catalysts on carbon supports. When using 2 as the substrate, 1 was obtained in 99.9 % at 8 % conversion (120°C, 34 bar, 4 h).…”
Section: 6-hexanediolmentioning
confidence: 99%
“…The use of biomass substantially reduces net carbon dioxide emissions because the latter is recycled in biomass production. Stoichiometric methods for the deoxydehydration of diols are abundant [10,11] but catalytic methods are limited [12][13][14][15][16]. Hydrogenolysis of polyols by various heterogeneous catalytic systems has been recently reported [17,18].…”
Section: Introductionmentioning
confidence: 99%